Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan Outsourching pada Perusahaan Penyedia Jasa Outsourching - Darmadi, Darmadi; Suryani, N Lilis; Syatoto, Iman; Guruh, Muhamad; Gunarda, Gunarda (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to examine the impact of motivation and work discipline on the performance of outsourcing employees at a service provider company in South Tangerang. A descriptive method with an associative nature and a quantitative approach was used to test population parameters through statistics. The population consists of 109 outsourcing cleaning service employees at PT. Siaga Mandatama Karya in 2019, with a saturated sample. Data analysis included validity, reliability, normality, multicollinearity, autocorrelation, heteroscedasticity, multiple linear regression, correlation coefficient, coefficient of determination, t-test, and F-test. The results show that motivation has a significant and positive impact on employee performance, with a strong correlation between the two variables. Work discipline also has a significant and positive effect on employee performance, indicating a strong relationship between them. When both motivation and work discipline are considered together, they have a significant and positive effect on employee performance. The analysis shows a strong relationship between the independent variables (motivation and work discipline) and the dependent variable (employee performance). The coefficient of determination indicates that motivation and work discipline contribute significantly to employee performance, while other factors also influence it. In conclusion, motivation and work discipline have a significant and positive effect on the performance of outsourcing employees at the service provider company in South Tangerang.